KAJIAN FASILITAS UMUM DESA MOROSARI DEMAK - Resza Riskiyanto; Arnis Rochma Harani; Rasyita Atmoko; Muhammad Ismail Hasan (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Life's demands continue together with deteriorating natural conditions cause the community adjust its